Sparking collaboration and instilling core competencies through training a statewide workforce in Infant Mental Health: Report from the field. Issue 3 (5th May 2021) - Dealy, Jennifer; Robinson, JoAnn; Eaves, Tanika; Maderia, Heidi
ABSTRACT: Fostering collaboration and instilling core competencies across the diverse Infant Mental Health systems and understanding their training needs are crucial endeavors to support the delivery of evidence‐based care and treatment continuity for infants and their families. This paper details the Connecticut Association for Infant Mental Health's use of a comprehensive infant mental health training series as a vehicle to achieve these aims. The training series, and the steps taken to execute and evaluate it are described to provide a framework for future collaborative training initiatives. Evaluation efforts were designed to address knowledge sought and gained and included pre and posttraining tests, participant reports of their training goals and needs, and interviews with trainers regarding the series' strengths and limitations. Findings suggest significant improvements in participants' knowledge of training content across trainings. Participants indicated a desire for trainings on working with the whole family and their plan to integrate skills from the training into their work. Recommendations from trainers and evaluators are provided to spark future trainings and collaborative efforts. RESUMEN: Fomentar la colaboración e inculcar las competencias centrales entre los diversos sistemas de Salud Mental Infantil, así como comprender las necesidades de entrenamiento son iniciativas cruciales para apoyar la continuidad del ofrecimiento del cuidado y el tratamiento con base en la evidencia para infantes y sus familias. Este ensayo detalla el uso de una serie de entrenamientos de salud mental infantil comprensiva de la Asociación de Connecticut para la Salud Mental Infantil como un vehículo para lograr las metas mencionadas. La serie de entrenamientos y los pasos que se toman para ejecutarlo y evaluarlo se describen para aportar un marco de trabajo para futuras iniciativas colaborativas de entrenamiento. Los esfuerzos de evaluación se diseñaron para tomar en cuenta el conocimiento que se busca y se recibe e incluyeron exámenes previos y posteriores al entrenamiento, el reporte de los participantes sobre sus metas y necesidades en el entrenamiento, así como entrevistas con entrenadores acerca de los puntos fuertes y limitaciones de la serie. Los resultados sugieren mejoras significativas en cuanto al conocimiento de los participantes acerca del contenido del entrenamiento a lo largo de las sesiones de entrenamiento. Los participantes manifestaron su deseo de ser entrenados en trabajar con la familia entera y su plan de integrar habilidades aprendidas en el entrenamiento en su trabajo. Se incluyen las recomendaciones de los entrenadores y evaluadores con el fin de motivar futuros entrenamientos y esfuerzos colaborativos. RÉSUMÉ: Le fait de cultiver des collaborations et le fait d'instiller des compétences fondamentales au travers des divers systèmes de Santé Mentale du Nourrisson, tout comme le fait de comprendre leurs besoins en formation sont des tentatives cruciales de soutenir la prestation de soins factuels et la continuité de traitement pour les nourrissons et leurs familles. Cet article détaille l'utilisation qu'a faite l'Association de Santé Mentale du Nourrisson de l'état du Connecticut aux Etats‐Unis d'une série de formation complète en santé mentale du nourrisson en tant que véhicule afin d'achever ces buts. La série de formation et les mesures prises pour la mettre en place et l'évaluer sont ici décrites afin d'offrir une structure d'initiatives collaboratives de formation. Les efforts d'évaluation ont été conçus afin d'aborder les connaissances désirées et acquises et ont inclus des tests pré‐ et post‐formation, des rapports des participants sur leurs buts et leurs besoins de formation, et des entretiens avec les formateurs concernant les points forts et les limitations de la série. Les résultats suggèrent des améliorations importantes dans les connaissances sur le contenu de la formation de la part des participants au travers des formation. Les participants ont indiqué le désir de formation sur le travail avec toute la famille et les intentions qu'ils avaient d'intégrer les compétences acquises durant la formation dans leur travail. Des recommandations pour les formateurs et les évaluateurs sont présentées afin de faire naître dans le future d'autres formations et efforts collaboratifs. ZUSAMMENFASSUNG: Durch eine landesweite Personalschulung in psychischer Säuglingsgesundheit Zusammenarbeit fördern und Kernkompetenzen vermitteln: ein Bericht aus der Praxis Es ist entscheidend, in den verschieden Säuglingsgesundheitsstrukturen Zusammenarbeit zu fördernd, Kernkompetenzen zu vermitteln und den Schulungsbedarf zu erfassen, um die Gewährleistung einer evidenzbasierten Pflege‐ und Behandlungskontinuität für Säuglinge und ihre Familien unterstützen zu können. In diesem Paper wird beschrieben, wie die Connecticut Association for Infant Mental Health eine umfassende Schulungsreihe zur psychischen Gesundheit von Säuglingen einsetzt, um dieses Ziel zu erreichen. Die Schulungsreihe sowie deren Durchführung und Evaluation werden beschrieben, um einen Rahmen für zukünftige kollaborative Schulungsinitiativen zu schaffen. Die Evaluation zielte darauf ab, angestrebtes und gewonnenes Wissen zu erfassen. Sie umfasste Prä‐ und Posttests, Berichte der Teilnehmenden über ihre Schulungsziele und ‐bedürfnisse sowie Interviews mit Anleiter:innen über die Stärken und Grenzen der Schulungsserie. Die Ergebnisse deuten darauf hin, dass das Wissen der Teilnehmenden über Schulungsinhalte in allen Schulungen erheblich verbessert wurde. Die Teilnehmenden äußerten den Wunsch nach Schulungen zur Arbeit mit der ganzen Familie und zur Integration der erlernten Fähigkeiten in ihre Arbeit. Empfehlungen von Anleiter:innen und Evaluator:innen werden gegeben, um zukünftige Schulungen und kollaborative Bestrebungen in Gang zu setzen. 抄録: 乳幼児精神保健における全州労働力研修を通じた連携の促進とコアコンピテンシー (中核能力) の浸透:現場からの報告 多様な乳幼児の精神保健システム全体において、連携を促進しコアコンピテンシー (中核能力) を浸透させ、その研修ニーズを把握することは、乳幼児とその家族にエビデンスに基づいたケアと治療の継続性を提供するために極めて重要な取り組みである。この論文では、コネチカット州の乳幼児精神保健協会が、これらの目的を達成するための手段として、包括的な乳幼児精神保健のシリーズ研修を利用していることについて詳細を述べている。将来の共同研修構想の枠組みを提供するために、シリーズ研修とそれを実行・評価するための手順が説明されている。評価の取り組みは、求められ、得られた知識に対処するように設計されており、研修前後のテスト、研修の目標とニーズに関する参加者のレポート、シリーズ研修の長所と限界に関する指導者への面接が含まれていた。調査結果は、研修全体を通して研修内容に関する参加者の知識が大幅に向上したことを示唆している。参加者からは、家族全体への働きかけに関する研修への希望や、研修で得たスキルを仕事に統合する計画が示された。指導者と評価者からの助言が、将来の研修と連携作業を促進するために提供される。 摘要: 在各种婴儿心理健康系统中促进协作并培养核心竞争力, 了解他们的培训需求, 是为婴儿及其家庭提供循证护理和治疗连续性的关键性工作。本文详细介绍了康涅狄格州婴儿心理健康协会使用综合性的婴儿心理健康系列培训作为实现这些目标的手段。该系列培训, 以及执行和评估该培训所采取的步骤, 旨在为未来的协作培训计划提供一个框架。评估工作旨在处理寻求和获得的知识, 包括培训前后的测试、参与者关于其培训目标和需求的报告, 以及与培训师就该系列培训的优点和局限性进行的访谈。研究结果表明, 参与者对培训内容的了解在培训过程中有了显著的提高。参与者表示希望与全家一起进行培训, 并计划将培训中的技能融入他们的工作中。文章提供了培训师和评估人员的建议, 以激发未来的培训和协作尝试。 ملخص: تعزيز التعاون وغرس الكفاءات الأساسية من خلال تدريب قوة عاملة على مستوى الولاية في مجال الصحة النفسية للرضع: تقرير من الميدان يعتبر تعزيز التعاون وغرس الكفاءات الأساسية عبر أنظمة الصحة النفسية المتنوعة للرضع وفهم احتياجاتهم التدريبية عناصر هامة لدعم تقديم الرعاية القائمة على الأدلة واستمرارية العلاج للرضع وأسرهم. تفصّل هذه الدراسة استخدام جمعية كونيتيكت للصحة النفسية للرضع سلسلة شاملة للتدريب على الصحة النفسية للرضع كوسيلة لتحقيق هذه الأهداف. ونقدم وصفاً لسلسلة التدريب والخطوات المتخذة لتنفيذها وتقييمها لتوفير إطار لمبادرات التدريب التعاوني في المستقبل. وتم تصميم جوانب التقييم لمعالجة المعارف التي تم الحصول عليها والتي تم اكتسابها، واشتملت على اختبارات ما قبل التدريب وما بعده، وتقارير المشاركين عن أهدافهم واحتياجاتهم التدريبية، ومقابلات مع المدربين بشأن نقاط القوة والضعف في برنامج التدريب. وتشير النتائج إلى حدوث تحسنات كبيرة في معرفة المشاركين بمحتوى التدريب من خلال الدورات التدريبية. وأشار المشاركون إلى رغبتهم في الحصول على تدريب للعمل مع جميع أفراد الأسرة، وعن خطتهم لإدماج المهارات التي يتم الحصول عليها من التدريب في عملهم. تقدم الدراسة توصيات من المدربين والمقيِّمين للتشجيع على المزيد من البرامج التدريبية والجهود التعاونية في المستقبل.